A conceptual model of organisational innovation in Malaysia. (17th April 2019) - Kumar, Raj; Chaw, Lee Yen; Kwek, Choon Ling
Since innovation is widely regarded as an imperative foundation for competitive advantage in today's vigorously changing environment, organisations need to put high consideration towards the adoption of innovation and consider organisational innovation as part and partial of their strategic plans and daily activities. Based on the literature review, a conceptual model with a set of proposed constructs such as human resource management, social capital and organisational learning mediated by entrepreneurial orientation is analysed. These constructs are adopted in this research to facilitate the adoption and achievement of organisational innovation among the small and medium enterprises (SMEs) in Malaysia. Therefore, the main objective behind this paper is to examine the relationships among the proposed constructs of human resource management, organisational learning, social capital and marketing effect of entrepreneurial orientation towards enhancing organisational innovation in the context of small and medium enterprises in Malaysia.